The Lifetime Medical Cost Savings from Preventing HIV in the United States - Schackman, Bruce R. (Med Care, 2015)
OBJECTIVE: Enhanced HIV prevention interventions, such as pre-exposure prophylaxis for high-risk individuals, require substantial investments. We sought to estimate the medical cost saved by averting one HIV infection in the United States. METHODS: We estimated lifetime medical costs in persons with and without HIV to determine the cost saved by preventing one HIV infection. We used a computer simulation model of HIV disease and treatment (CEPAC) to project CD4 cell count, antiretroviral treatment status, and mortality after HIV infection. Annual medical cost estimates for HIV-infected persons, adjusted for age, sex, race/ethnicity, and transmission risk group, were from the HIV Research Network (range $1,854–$4,545/month) and for HIV-uninfected persons were from the Medical Expenditure Panel Survey (range $73–$628/month). Results are reported as lifetime medical costs from the US health system perspective discounted at 3% (2012 US dollars). RESULTS: The estimated discounted lifetime cost for persons who become HIV infected at age 35 is $326,500 (60% for antiretroviral medications, 15% for other medications, 25% non-drug costs). For individuals who remain uninfected but at high risk for infection, the discounted lifetime cost estimate is $96,700. The medical cost saved by avoiding one HIV infection is $229,800. The cost saved would reach $338,400 if all HIV-infected individuals presented early and remained in care. Cost savings are higher taking into account secondary infections avoided and lower if HIV infections are temporarily delayed rather than permanently avoided. CONCLUSIONS: The economic value of HIV prevention in the US is substantial given the high cost of HIV disease treatment.